KETERAMPILAN BERPIKIR KREATIF PADA PEWARNAAN TITIK r-DINAMIS GRAF HASIL OPERASI EDGE CORONA GRAF LINTASAN - Liowardani, Adelia Putri; Dafik, D; Fatahillah, Arif (Department of Mathematics Education , University of Jember, 2018)
Abstract This Research is development from vertex r-dynamic coloring for every simple and connected graph. Vertex r-dynamic coloring of graph G such that the neighbors of any vertex v receive at least min different colors. The r-dyanamic chromatic number written as . In this research we use edge corona product graph. Edge corona product of G and H as denoted by Let G and H is simple and connected graph, is obtained by taking graphs H as many copies edge of graph G and connected graphs H on two vertices edge of G. In this research will also related with creative thinking skills with four aspects as indicator. Those aspects are Fluency, Flexibility, Orisinality, and Elaboration. The results of this research is theorem about vertex r-dynamic coloring on edge corona product and related with creative thinking skills. Keywords: Vertex r-dynamic coloring, edge corona, creative thinking skills